Cancer Stem Cells and Neuroblastoma: Characteristics and Therapeutic Targeting Options - Veronica Veschi; Veronica Veschi; Francesco Verona; Carol J. Thiele (Frontiers in Endocrinology, 2019)
The majority of embryonal tumors or childhood blastomas derive from pluripotent progenitors or fetal stem cells that acquire cancer stem cell (CSC) properties: multipotency, self-renewal ability, metastatic potential, chemoresistance, more pronounced levels of drug transporters, enhanced DNA-damage repair mechanisms, and a quiescent state. Neuroblastoma (NB) is considered a neuroendocrine tumor and is the most common extracranial neoplasm in children. NB pathogenesis has frequently been associated with epigenetic dysregulation and a failure to implement a differentiation program. The origin, characteristics, and isolation of the CSC subpopulation in NB are still incompletely understood, despite the evidence that this cell subset contributes to disease recurrence and acquired resistance to standard therapies. Here, we summarize the literature regarding the isolation and characterization of CSCs in NB over the past decades, from the early recognition of the expression of stem cell factor (SCF) or its receptor c-KIT to more recent studies identifying the ability of G-CSF and STAT3 to support stem cell-like properties in NB cells. Additionally, we review the morphological variants of NB tumors whose recent epigenetic analyses have shed light on the tumor heterogeneity so common in NB. NB-derived mesenchymal stem cells have recently been isolated from primary tumors of NB patients and associated with a pro-tumorigenic role in the tumor microenvironment, enabling immune escape by tumors, and contributing to their invasive and metastatic capabilities. In particular, we will focus on epigenetic reprogramming in the CSC subpopulation in NB and strategies to target CSCs in NB.